2002
DOI: 10.1253/circj.66.1070
|View full text |Cite
|
Sign up to set email alerts
|

Shoshin Beriberi With Vasospastic Angina Pectoris. Possible Mechanism of Mid-Ventricular Obstruction.

Abstract: eriberi heart is a very rare disease today and is caused by thiamin deficiency. 1 Beriberi heart is hemodynamically characterized by high cardiac output failure associated with arteriolar vasodilatation. Shoshin beriberi is a fulminant form of beriberi heart and is characterized by hypotension, tachycardia, and lactic acidosis. [1][2][3][4][5][6][7] Initially, mid-ventricular obstruction had been reported as a special form of hypertrophic cardiomyopathy, but it can be found in other conditions such as myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Previous reports have shown that 100-200 mg/day of thiamine generally improves the symptoms of Shoshin beriberi. 4,5,18) Doses of thiamine used for Shoshin beriberi in the present study were comparable to those reported in previous studies. The present study showed that alcohol-related diseases were the most common comorbidities in patients with Shoshin beriberi, followed by diabetes mellitus, depression, schizophrenia, dementia, and anorexia.…”
Section: Discussionsupporting
confidence: 89%
“…Previous reports have shown that 100-200 mg/day of thiamine generally improves the symptoms of Shoshin beriberi. 4,5,18) Doses of thiamine used for Shoshin beriberi in the present study were comparable to those reported in previous studies. The present study showed that alcohol-related diseases were the most common comorbidities in patients with Shoshin beriberi, followed by diabetes mellitus, depression, schizophrenia, dementia, and anorexia.…”
Section: Discussionsupporting
confidence: 89%
“…Acute myocardial infarction in patients with normal coronary arteries may occur via transient occlusion of coronary vessel(s) by spasm and/or thrombus (15). Indeed, a previous case report described a case of vasospastic angina in a patient with Shoshin beriberi (16). In the present case, spasm of coronary arteries was not induced by provocation test.…”
Section: Discussionmentioning
confidence: 50%
“…We conducted a literature review using PubMed and Google Scholar. English language case reports published between 1990 and 2017 were reviewed using the search terms” beriberi,”” shock,” and” thiamine.” The review identified five articles describing ScvO 2 [ 4 , 9 12 ]. Each case described high ScvO 2 (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%